2009
DOI: 10.1021/cm900395k
|View full text |Cite
|
Sign up to set email alerts
|

Li Storage Properties of Disordered Graphene Nanosheets

Abstract: Graphene has aroused intensive interest because of its unique structure, superior properties, and various promising applications. Graphene nanostructures with significant disorder and defects have been considered to be poor materials because disorder and defects lower their electrical conductivity. In this paper, we report that highly disordered graphene nanosheets can find promising applications in high-capacity Li ion batteries because of their exceptionally high reversible capacities (794−1054 mA h/g) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
698
3
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 996 publications
(724 citation statements)
references
References 35 publications
19
698
3
4
Order By: Relevance
“…[32][33][34][35][36] In these papers, the rather poor reversibility and the limited number of cycles verifi ed the drawbacks initially observed by I. Honma. [ 28 ] Specifi cally, Z. Jiao et al [ 34 ] correlated the sensitivity of RGO's Li + storage properties to the method of GO reduction employed (i.e., thermal reduction in N 2 at different temperatures, chemical reduction with hydrazine and electron beam irradiation, see Table 1 ). They also showed that the high specifi c surface area (SSA) of RGO, which was generally considered a benefi cial property of these classes of materials, [ 3 ] in this specifi c case represented a drawback.…”
Section: Graphene As Li-ion Hostmentioning
confidence: 53%
“…[32][33][34][35][36] In these papers, the rather poor reversibility and the limited number of cycles verifi ed the drawbacks initially observed by I. Honma. [ 28 ] Specifi cally, Z. Jiao et al [ 34 ] correlated the sensitivity of RGO's Li + storage properties to the method of GO reduction employed (i.e., thermal reduction in N 2 at different temperatures, chemical reduction with hydrazine and electron beam irradiation, see Table 1 ). They also showed that the high specifi c surface area (SSA) of RGO, which was generally considered a benefi cial property of these classes of materials, [ 3 ] in this specifi c case represented a drawback.…”
Section: Graphene As Li-ion Hostmentioning
confidence: 53%
“…In fact, the intercalation of Li þ ions into graphite is typically seen in the electrochemical process occurring in a graphite anode; nevertheless, the theoretical capacity is B372 mAh g À 1 and the reversible intercalation of lithium in graphite occurs at only B0.1 V that is far to the 3.4 V. Highly disordered graphene nanosheets have been shown to exhibit a higher reversible Li þ ion storage capacity up to 1,100 mAh g À 1 . However, the charge/ discharge profiles should be with a large voltage hysteresis and without distinct potential plateaus 33 . These indicate that there should exist another Li þ ion storage mechanism for the observed high capacity from EG.…”
Section: Resultsmentioning
confidence: 99%
“…The first cycle reversible capacity of non-reduced electrode at the current density of 10 mA·g −1 equals 136 mAh·g −1 , but such capacity rapidly decreases to 105 mAh·g −1 just in 5 th cycle. Such rapid decreasing of the capacity is a typical behavior for all disordered carbons, especially rGO [11][12][13][14][15]. Higher current densities induce further capacity decreasing up to slightly above 30 mAh·g −1 for current density of 100 mA·g −1 .…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Currently, rGO is strongly investigated for the usage in LIBs either as an additive for developing electrical contact [10] or an aid during the synthesis of electrode material [11] as well as an electrode active material [12][13][14][15][16]. Pure rGO used as LIBs anode exhibits high capacity, few times higher than graphite.…”
Section: Introductionmentioning
confidence: 99%